KNOWLEDGE RESIDES IN CONSENSUS: HOW EXTREMISTS TRY TO CONTROL TRUTH THROUGH SOCIAL DYNAMICS - J.M. Berger (The Journal of Intelligence, Conflict and Warfare)
On November 21, 2024, Dr. J.M. Berger presented Knowledge Resides in Consensus: How Extremists Try to Control Truth Through Social Dynamics for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were how extremism can be defined as related to intergroup conflict, how the age of the internet has made it easier for extremist groups to push out propaganda and exploit microtargeting to flourish, and how extremism exploits a desire for cognitive security.